Possible role of matrix metalloproteinases in reconstruction of peripheral pulmonary arteries induced by hypoxia - Novotná, J; Herget, J (Physiological research, 2002)
Exposure to chronic hypoxia results in hypoxic pulmonary hypertension characterized by structural remodeling of peripheral pulmonary vasculature. An important part of this remodeling is an increase of collagen turnover and deposition of newly formed collagen fibrils in the vascular walls. The activity of collagenolytic metalloproteinases in the lung tissue is notably increased in the first days of exposure to hypoxia. The increased collagenolytic activity results in the appearance of collagen cleavages, which may be implied in the triggering of mesenchymal proliferation in peripheral pulmonary arteries. We hypothesize that radical injury to pulmonary vascular walls is involved in collagenolytic metalloproteinase activation.
Keywords: extracelulární matrix; Animals; Collagen; Extracellular Matrix; chronická nemoc; hypoxie; lidé; Hypoxia; kolagen; zvířata; Pulmonary Artery; matrixové metaloproteinasy; Chronic Disease; Matrix Metalloproteinases; arteria pulmonalis; Humans